2018
DOI: 10.4085/1062-6050-52.11.29
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Athletic Trainers' Knowledge of the Female Athlete Triad and Relative Energy Deficiency in Sport

Abstract: Continuing education for ATs about the Triad and RED-S may encourage a more comprehensive approach to referral and screening after a diagnosis of menstrual dysfunction or bone-stress injury. Using institutional opportunities, such as preparticipation screening, for identifying components of the Triad or RED-S and specifying protocols for referring athletes who screen positive for 1 of these components should also be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 22 publications
(21 reference statements)
2
38
0
1
Order By: Relevance
“…Research published in the past four years has established that low EA is more easily and accurately identified by the use of surrogate markers including suppressed resting RMR [27,38,43] and validated questionnaires that screen for a drive for thinness and physiological symptoms associated with low EA [30]. Understanding athletes' and coaches' knowledge and perspectives on low EA and its health and performance consequences is required [10]. Few education initiatives exist to improve athlete understanding of low EA and its associated health and performance consequences [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research published in the past four years has established that low EA is more easily and accurately identified by the use of surrogate markers including suppressed resting RMR [27,38,43] and validated questionnaires that screen for a drive for thinness and physiological symptoms associated with low EA [30]. Understanding athletes' and coaches' knowledge and perspectives on low EA and its health and performance consequences is required [10]. Few education initiatives exist to improve athlete understanding of low EA and its associated health and performance consequences [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little research exploring the knowledge coaches have on this topic. A recent cross-sectional survey that investigated knowledge of the Triad and RED-S among head athletic trainers at National Collegiate Athletic Association (NCAA) member institutions reported that almost all principal athletic trainers (98.6%) were aware of the Triad [10]. Only one-third (33%) were aware of RED-S [10].…”
Section: Knowledge Of Low Energy Availability and Relative Energy Defmentioning
confidence: 99%
See 2 more Smart Citations
“…This stress has been associated with changes in dietary behavior by the athlete resulting in severe food restriction, capable of developing into one of the components of the triad, eating disorders. The etiology of another component, menstrual dysfunction, although it is multifactorial, is directly related to a restricted caloric intake, negative energy balance, low energy availability, sudden onset of vigorous exercise, and others (Kroshus, et al, 2018;Marcason, 2016), triggering menstrual and bone dysfunction. Therefore, in these conditions, female TALITA ADÃO PERINI DE OLIVEIRA, GLAUBER LAMEIRA DE OLIVEIRA, JOÃO RAFAEL VALENTIN-SILVA, ESTÉLIO HENRIQUE MARTINS DANTAS, JOSÉ FERNANDES FILHO -…”
Section: The Female Athlete Triad Syndromementioning
confidence: 99%